Business Development Strategy of “Healthfull” Brand Products Using SWOT-AHP Analyses - Putri, Belia Berliani; Perwitasari, Sophia Dwiratna Nur; Pratopo, Lukito Hasta (School of Business, Bogor Agricultural University (SB-IPB), 2024)
In recent years, public awareness of adopting a healthy lifestyle has increased, as shown by the increase in fruit and vegetable consumption one of the business activities at PT. Hydroponics Padjadjaran Indonesia produces and sells cold-pressed juice and salad under the brand